PEMETAAN WILAYAH RAWAN BANJIR DI KOTA MANADO DENGAN MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS - Syanet Renwarin; Jeanne Lengkong; Tommy Sondakh; Jailani Husain (COCOS, 2014)
sistem informasi geografis.ABSTRACThis study was conducted during one month (May 29, - June 29, 2014) andimplemented in the city of Manado. This study aims to analyze the flood prone areas in thecity of Manado in order to obtain the level of vulnerability and dissemination of informationin the form of a map by using a Geographic Information System. The study was conducted byusing descriptive method which consists of collecting data and map overlay. While theidentification of flood-prone areas using the method by Hematang (2011). Parametersmeasured were soil type, slope, land use and rainfall. The results of this study show the studyarea prone to flooding in the city of Manado has not vulnerable flood level (an area of603.34 ha), the vulnerability of being (an area of 5467.01 ha), are not susceptible (coveringan area of 6492.39 ha) and the rate is very susceptible (an area of 2180.11 ha) spread in 10districts namely Bunaken, Malalayang, Mapanget, Sario, Singkil, Paal Dua, Tikala,Tuminting, Wanea and Wenang.Key Word : mapping, flood, geographic information system